Peran Kiai Dalam Menyelesaikan Konflik Keluarga - Muhammad Habib; Muhammad Shaleh; Muhammad Hasbi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
An interesting phenomenon that occurs in the people of the Tanjung Pura Subdistrict, Langkat Regency, who still consider the kiai to be a highly respected and respected figure. In terms of problems that occur between husband and wife such as nusyuz and syiqaq, people still believe that by telling the kiai, they will get the best solution as an effort to resolve conflicts that occur in their families. This type of research is juridical-empirical law research (Socio-Legal Research). This research was conducted by looking for field data (field research) and library research, namely analyzing data sources on books. Data collection techniques were carried out by conducting interviews with kiai and communities in several villages in the Tanjung Pura District, Langkat Regency. The purpose of this study was to determine the role played by the kiai in resolving family conflicts in Tanjung Pura District, Langkat Regency and to find out the review of Islamic law and its legislation related to the resolution of family conflicts involving a kiai. The results of the research that have been carried out conclude that the kiai has a role in reducing family conflicts in the community in the Tanjung Pura District, Langkat Regency, including the first role of the kiai in providing good solutions to problems faced by married couples, secondly the role of the kiai in trying to reconcile husband and wife. -wife who is in disagreement, the three roles of the kiai are good protectors in an effort to resolve family conflicts. Islam gives up the freedom of settlement to reach an agreement to make peace for those who are in dispute. This is done because Islah-shulh is part of Islamic teachings to resolve a dispute or conflict peacefully. However, it is different from the laws and regulations which have their own rules in the implementation of mediation in court. In accordance with Perma No. 1 of 2016 Article 13 that to be a mediator in the mediation process must have a certificate. With regard to efforts to resolve family conflicts by involving the kiai as hakam, this is permissible. However, the role of the kiai as a mediator or hakam can only be carried out in an effort to resolve disputes that have not been submitted to court with the consent of the conflicting parties. Unless, the kiai already has a certificate as a mediator. Keywords: kiai; mediator; Family